Menumbuhkan Kesadaran Berbangsa dan Bernegara Melalui Pendidikan Kewarganegaraan di Era Digital - Agum Murtaib; Melki Wijaya; Sarifah Aini Hasibuan; Yolanda Citra; Ilham Hudi (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Citizenship is becoming increasingly important as an integral part of individual and societal identity in the digital era. The purpose of this short report is to discuss and provide insight into the importance of comprehensive citizenship education to strengthen the spirit of citizenship in the digital era. Comprehensive citizenship education is essential to protect your rights and responsibilities as a citizen of the country. Emphasis is placed on character development and a positive attitude towards the Information technology and citizenship available today. Through comprehensive citizenship education, the next generation can develop awareness and active participation in a democracy that is responsive and inclusive in the use of information and technology